Cyclin E overexpression as a biomarker for combination treatment strategies in inflammatory breast cancer - Alexander, Angela; Karakas, Cansu; Chen, Xian; Carey, Jason P.W.; Yi, Min; Bondy, Melissa; Thompson, Patricia; Cheung, Kwok-Leung; Ellis, Ian O.; Gong, Yun; Krishnamurthy, Savitri; Alvarez, Ricardo H.; et al. (Impact Journals, 2017)
Inflammatory breast cancer (IBC) is a virulent form of breast cancer, and novel treatment strategies are urgently needed. Immunohistochemical analysis of tumors from women with a clinical diagnosis of IBC (n = 147) and those with non-IBC breast cancer (n = 2510) revealed that, whereas in non-IBC cases cytoplasmic cyclin E was highly correlated with poor prognosis (P < 0.001), in IBC cases both nuclear and cytoplasmic cyclin E were indicative of poor prognosis. These results underscored the utility of the cyclin E/CDK2 complex as a novel target for treatment. Because IBC cell lines were highly sensitive to the CDK2 inhibitors dinaciclib and meriolin 5, we developed a high-throughput survival assay (HTSA) to design novel sequential combination strategies based on the presence of cyclin E and CDK2. Using a 14-cell-line panel, we found that dinaciclib potentiated the activity of DNA-damaging chemotherapies treated in a sequence of dinaciclib followed by chemotherapy, whereas this was not true for paclitaxel. We also identified a signature of DNA repair–related genes that are downregulated by dinaciclib, suggesting that global DNA repair is inhibited and that prolonged DNA damage leads to apoptosis. Taken together, our findings argue that CDK2-targeted combinations may be viable strategies in IBC worthy of future clinical investigation.